Lyme Disease: The Threat of a Tick Born Illness - Nath, Ayana Shylaja; Ajith, Bhargavan (Indian Journal of Pharmacy Practice)
Lyme disease, which is the most common vector born disease caused by the Borrelia burgdorferi and transmitted in the United States primarily by Ixodes scapularis. The major symptoms of the disease are Erythema migrans, fatigue, malaise, myalgia, headache and regional lymphadenopathy. The untreated Lyme disease can spread to heart and nervous system, which lead to potentially life-threatening neurologic and cardiac problems.1 Lack of awareness and misdiagnosis is frequent which is the most common cause of failure of treatment. The study attempts to give a thorough knowledge and awareness about the Lyme disease by interpreting the clinical symptoms, pathophysiology, diagnostic criteria, potential therapies and prophylaxis.
Keywords: Lyme disease; Borrelia burgdorferi; Erythema migrans; Ixodes scapularis